Cantando, lendo a Bíblia, orando: as Escolas Bíblicas Dominicais como estratégia de implantação das confissões de fé protestantes em solo brasileiro. - Nascimento, Rebeca Araújo Carvalho (2023)
This paper intends to present a panoramic and theological view of what has been written and studied about the Sunday School, making the connection of its development in Brazil. That is, regarding its strategic role in the consolidation of the Brazilian mission Protestantism, in the middle of the 19th century and beginning of the 20th century, through the Sunday School textbooks. In this sense, this research has as a general objective: To identify, demonstrate and analyze the importance of the pedagogical process historically known as Sunday School that. through songs, Bible reading and the practice of prayer, was adopted as one of the strategies of implantation of Protestantism in Brazilian soil, in the mid-nineteenth century and early twentieth century. It aims to demonstrate, by comparing them, the models implanted in Brazilian soil, with classical models from the Anglo-Saxon world, seeking the explanations and justifications of eventual adaptative changes to the social reality of the converts, in the construction of a new habitus and the conquest of a new field, in the midst of a society where popular Catholicism had reigned for centuries. The analysis of the bibliographical corpus of the research allowed the rediscovery of certain textbooks that, based on the Bible, print the perspective of the Protestantism of North-American missionary origin, notably the Congregational and Baptist groups; the pedagogical bias of these textbooks reveals a new confession of faith and religion that was emerging in Brazil during the above-mentioned period. Furthermore, regarding the results: the missionary educational strategies of the North-American Sunday Schools in Brazil cannot be dissociated from the North-American expansion project itself: the "manifest destiny" of the mid 19th century. The Sunday Schools founded in Brazil at that time were born linked to the missionary idealism of the Congregationals, Presbyterians and Baptists for the evangelization of Brazil. We adopted as methodological procedures the historical research of bibliographical character, electing as theoretical reference the authors discussed in the field of Religion Sciences, among them, P. Bourdieu, A. G. Mendonça and P. Garcez, also using the conceptualization of M. de Certeau, regarding the strategy.